PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SD NEGERI 37 PEKANBARU - H, Kristin Sabatini; ', Syahrilfuddin; N, Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to improved mathematic learning learning outcomes with cooperative model numbered heads together type of students in class VA SDN 37 Pekanbaru. This research is classroomaction research (PTK), with the subject of research was student class VA SDN 37 Pekanbaru. The object of this research was implementation of mathematics learning to improv mathematics learning learning outcomes with cooperative learning model numbered heads together type. The result of research showed that mathematics learning thourgh cooperatice learning model numbered heads together type can improve mathematics learning learning outcomes. It was evident from : (1)learning activities of teacher increase from percentage of first cycle are 64,58% (good category) , on the second cycles becomes 89,58% (very good category); (2) learning activities of students increase from percentage of first cycle are 66,66% (good category) , on the second cycles becomes 89,58% (vey good category); (3) learning outcomes increase from average value pre action are 71,17 with completion value 43,24% (not complete), increased on first cycles amount 14,86% with value 81,71 (high category), and increased on second cycle amount 21,39% with value 86,35 (high category),with the result in increased for all mathematics learning learning outcomes are 36,25%.Key words : Numbered Heads Together, learning outcomes, implementation of learning.